Relação entre professores e alunos com dificuldades de aprendizagem e comportamento: uma história de mudanças - Najle, Carolina Paz Muñoz (2008)
Interpersonal relations are not easy and teacher-pupil relation is one of those. This research shows the relations between teachers and pupils from a classroom with learning difficulties, violence and indiscipline and the changes that occurred after modifications in the ways the teachers acted and perceived the pupils. Interviews were conducted with teachers from a 1st year of a High-School class in a government school of São Paulo City. Categories were created based on the interviews and the main issues were shown, such as how the family and the teenager react towards school, how the relationship between the teacher and the class was, teachers feelings of anxiety and insecurity, change proposals and their results for the relationships. It can be concluded that nowadays the school must pay attention to changes in youngsters, mainly focusing in teacher s formation and a proposal for a reflexive school.